PENGARUH TEKNOLOGI INFORMASI DALAM KEPROFESIAN DAN IMPLIKASINYA dalam DUNIA PENDIDIKAN: PENGARUH TEKNOLOGI INFORMASI DALAM KEPROFESIAN DAN IMPLIKASINYA DALAM DUNIA PENDIDIKAN - Muhammad Taufiq (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2017)
Accounting is an information system, more precisely; it is an application to the general theory of information to the problem of efficient economic operations. It also makes up a large part of the general information expressed in quantitative terms. In this context accounting is both a part of the general information system of an operating entity and a part of the basic field bounded by the concept of information If you work with a manual system and you want to see an account on given day, you have a paper file and you simply go to that particular section and pull out the file. When you’re on the computer system, in a sense all your accounts are kid of floating around in space. You can’t get your hands on them